2007
DOI: 10.1128/jb.01711-06
|View full text |Cite
|
Sign up to set email alerts
|

Initial Characterization of the Photosynthetic Apparatus of “ Candidatus Chlorothrix halophila,” a Filamentous, Anoxygenic Photoautotroph

Abstract: "Candidatus Chlorothrix halophila" is a recently described halophilic, filamentous, anoxygenic photoautotroph (J. A. Klappenbach and B. K. Pierson, Arch. Microbiol. 181:17-25, 2004) that was enriched from the hypersaline microbial mats at Guerrero Negro, Mexico. Analysis of the photosynthetic apparatus by negative staining, spectroscopy, and sodium dodecyl sulfate-polyacrylamide gel electrophoresis indicated that the photosynthetic apparatus in this organism has similarities to the photosynthetic apparatus in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
(36 reference statements)
1
8
0
Order By: Relevance
“…White bars show a 10 mm scale. not shown) suggested that this pigment was nearly absent in chlorosomes from both cultures as previously reported for other filamentous anoxygenic phototrophic bacteria (Gich et al, 2003;van de Meene et al, 2007).…”
Section: Enrich_sisóf2supporting
confidence: 82%
“…White bars show a 10 mm scale. not shown) suggested that this pigment was nearly absent in chlorosomes from both cultures as previously reported for other filamentous anoxygenic phototrophic bacteria (Gich et al, 2003;van de Meene et al, 2007).…”
Section: Enrich_sisóf2supporting
confidence: 82%
“…4A ). About 85% of the sequences of the Chloroflexi group belonged to Candidatus chlorothrix , a filamentous anoxygenic photoautotroph isolated from Guerrero Negro hypersaline mats in Mexico [37] whereas most of the Planctomycetes sequences belonged to the genus Phycisphaera . The remaining less dominant groups (≤3% of total sequences) were distributed among several other groups ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Phylogenetic analysis of 16S rRNA genes in general provides little information regarding metabolic traits. This is particularly true for Chloroflexi , which display a broad spectrum of lifestyle characteristics, e.g., anoxygenic photosynthesizers [ 16 , 17 ], obligate aerobic/anaerobic heterotrophs [ 18 21 ], thermophiles [ 18 , 20 , 22 ], halophiles [ 23 ], nitrite oxidizers [ 24 , 25 ], predators with gliding motility [ 26 ], some with capacity for reductive dehalogenation [ 27 , 28 ] and even endospore-forming Gram-positive bacteria in a largely Gram-negative phylum [ 29 , 30 ]. The only genomic information from the SAR202 group at present is from an incomplete single cell amplified genome (SAGs), Pac-SCGC-AAA240-N13, obtained from a depth of 770 m from the ALOHA station in the Pacific Ocean north of Hawaii [ 31 ] but no genomic analyzes have been reported.…”
Section: Introductionmentioning
confidence: 99%